E-Commerce Recommendation System - Samani, Yashraj; Satralkar, Ashutosh (E-COMMERCE FOR FUTURE & TRENDS, 2022)
In today’s era of instant transaction, everything is expected to be quick and fast paced and so is shopping. To achieve this, many companies are trying to lure their customers by providing recommendations through browsing cookies files stored by browser. It is imperative to know the customer, before recommending the product as relevant recommendation enlightens customers and thus may generate positive sentiment towards entity. This would boost the sales and the business. In today’s era, there are various types of recommendation algorithms; each has its own pros and cons towards the working. Big e-commerce giants like amazon, Flipkart, Myntra, etc. use the combination of different algorithms to get the best out of it. In this study we have seen some factors, working of algorithms, and some pros and cons in the existing system to verify if there exists any better approach for current system...?